Kommunikation und Netzwerkbildung mit den Mennoniten im Königlichen Preußen - aus den Herrnhuter Reiseberichten - Kodzik, Joanna (Unitas Fratrum, 2018)
Zinzendorf not only sought and achieved contact with the Mennonites in the Netherlands but also established relations with the Mennonites in Danzig, Elbing and Thorn in the Kingdom of Prussia, who had fled from the Netherlands. Conrad Lange made the first contacts in 1742 on his own initiative. In Danzig the house of the merchant Rosenbaum (d. 1776) became a base for the Moravians. The Jewish Christian David Kirchhof and his wife Esther Grünbeck became important for the Moravians, as did the Mennonites Abraham van Gammern and Carl Schröder, a trimming maker. The author quotes extensive passages from van Gammern's travel report of 1761, the last before the partition of Poland in 1772, and compares it with Lange's report of 1742. A description of the contents of these reports and their perspective on the Mennonites follows. In a concluding assessment, the author stresses that the Moravians' relationship with the Mennonites in Danzig opened up for them more opportunities for action than did their relationships with the Lutheran citizens, whose attitude towards them was critical, or with the influential aristocracy. Only towards the end of the eighteenth century did the Moravians come to a position of greater acceptance by the citizens of Danzig.